Assessment of Health Protective Behaviors among Patient with Thalassemia at the Women's and Children’s Hospital in Al-Muthanna City - Radha M. Lefta (Journal of Global Pharma Technology, 2018)
Background: Thalassemia is one of the most common disorders in the world, mostly in the region located around and nearby the Mediterranean Sea. People who are under 30 are most likely to have this disease and that's because of short life expectancy for thalassemia patients, due to life threatening complications and possibly the lack of health protective. Objectives: The study aimed to identify the health Protective behaviors through utilization (Nutrition, Drug, follow up, and Socio-Psychology) domains and to determine correlation between overall health protective behaviors and demographics data. Methodology: The study design a quantitative research by a descriptive study, the sampling it is non-Probability "purposive" sample  was conducted on 70 people with Thalassemia at the Women's and Children’s Hospital in Al-Muthanna City for the period from September 7, 2016 to February 16, 2017. A questionnaire it has used as a tool of data collection to fulfill the study, which consist of three parts, include demographic characteristics, medical history, and the health Protective behaviors. A content validity, which is carried out through 13 panels of experts .A panel of experts determines validity, while reliability use split half. A descriptive and inferential statistics are used to analyze the data. Results: The study indicates that the majority of patients have major thalassemia of the study sample are 60% and most   are male. The study sample are most age 5-10 year within age groups  (37.1%) with limited and average income its mild 54%. The study results indicate for assessment for health behaviors health follow-up and levels of drug use is inadequate. The study results depict that there is a significant between overall health protective behaviors and gender. Conclusions: The Study Sample conclusions have inadequate in health protective drug and follow-up domains due to inability to payment the cost of healthcare services because the majority of the study sample is income mild. Recommendations: To establish educational and awareness campaigns for patients and their patients about Thalassemia and to confirm the role of the nurse in actively participating in the guidance of patients.Keyword: Health Protective Behavior, Thalassemia, Drug use, Health follow-up.